Khaled Hailds Achievement, Believes Better Results To Come - The Star, Simrit Kaur & Karen Chapman (2008)
Malaysia's top local univerisites' improved ranking in The Times Higher Education-QS (THE-QS) World University Rankings 2008 is an achievement to be proud of said Higher Education Minister Datuk Seri Mohamed Khaled Nordin.